Organic Electroluminescent Materials Possessing Intra- and Intermolecular Hydrogen Bond Interactions: A Mini-Review - Liu, Xinyong; Li, Jingwei; Qiu, Xu; Pan, Yuyu (Frontiers in Chemistry, 2022)
Organic light-emitting diodes (OLEDs) have become the predominant technology in display applications because of their superior light weight, flexibility, power conservation, and environmental friendliness, among other reasons. The device’s performance is determined by the intrinsic properties of organic emitters. The aggregation structure of emitters, in particular, is crucial for color purity and efficiency. Intra- and intermolecular interactions, such as hydrogen bonds (H-bonds), can reduce structural vibrations and torsions, which affect the stability of emitting layer films and optoelectronic properties of emitting materials. Hence, by regulating the H-bond interaction, the desired properties could be obtained. This mini-review focuses on the influence of intra- and intermolecular H-bond interactions on the optoelectronic properties of high-performance emitters.